(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The study surveys the usage of modern pedagogical techniques in ESL classroom, which are applied by English teachers for the development of linguistic abilities of learners at Samarkand State Institute of Foreign Languages. The English language methodology keeps on exploring the ways and methods of teaching second language by using various techniques to ESL learners. The study focuses on the analysis of effectiveness of using innovative techniques for developing critical thinking abilities. The research study applies both quantitative and qualitative methods for data analysis. Participating subjects were 200 students of 2-3rd English course, beginning from intermediate to upper intermediate levels. The data from analysis manifests that the usage of up-to date techniques for developing critical thinking skills increase the effectiveness of English classes. Modern teaching techniques modify the role of the teacher from the transmission of information to the organizer and coordinator of the educational process and make it possible to form complex competencies in the future. Therefore, the purpose of the investigation is to implement some up-to date techniques in the syllabus of English classes. The objectives of the theses are the formation and developing critical thinking abilities of learners. The given results illustrates the growth of self-confidence, motivation and competence of students.